2014
DOI: 10.1111/ppa.12198
|View full text |Cite
|
Sign up to set email alerts
|

Biological control agents (BCAs) of verticillium wilt: influence of application rates and delivery method on plant protection, triggering of host defence mechanisms and rhizosphere populations of BCAs

Abstract: Verticillium dahliae causes severe yield reductions in a variety of important annual crops worldwide. Control of verticillium wilt has relied on soil fumigation; however, the use of the main soil fumigant, methyl bromide, has been banned in the European Union since 2010, creating a demand for novel crop protectants. As such, the use of biocontrol agents (BCAs) is an appealing management strategy. Prerequisites for the development of a successful BCA are an understanding of the modes of action of the antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 35 publications
1
52
0
Order By: Relevance
“…Other control strategies such as crop rotation, the usage of resistant plant species, and soil solarization have only limited efficiency (Haas and Défago, 2005; Depotter et al, 2016). They are either ineffective, time-consuming, costly, may have a severe environmental impact, or even could affect human health (Angelopoulou et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other control strategies such as crop rotation, the usage of resistant plant species, and soil solarization have only limited efficiency (Haas and Défago, 2005; Depotter et al, 2016). They are either ineffective, time-consuming, costly, may have a severe environmental impact, or even could affect human health (Angelopoulou et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some of these plant growth-promoting bacteria (PGPB) have been used as biological control agents against plant diseases and pests (Ahemad and Kibret, 2014). However, common fungal antagonistic bacteria such as Pseudomonas species have only limited inhibitory impact on Verticillium due to the long-term persistence of Verticillium microsclerotia in soil (Angelopoulou et al, 2014). Members of the endospore-forming genus Bacillus possess a high potential as new fungal antagonists.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, different research work demonstrated the potential of different antagonists like Thalaromyces flavus, Fusarium oxysporum and phomopsis sp. to control different Verticillium wilt in tomatoes, pistachio, cotton and eggplant (Marois et al, 1982;Tjamos et al, 2004;Zheng et al, 2011;Angelopoulou et al, 2014). Recently Yuan et al (2017) research work on biocontrol efficacy of Penicillium simplicissimum with DI = 41.4%, Acremonium sp with DI = 39.2%, Leptosphaeria sp.…”
Section: Reducing Verticillium Infestation On Eggplant Cultivarsmentioning
confidence: 99%
“…Effective bacterial antagonists include plant growth-promoting rhizobacteria, such as pseudomonads (Sharma and Novak., 1998) and other genera obtained from plant rhizospheres (Berg et al, 1994;Angelopoulou et al, 2014). Examples of fungi that have some efficacy include Pythium oligandrum (Al-Rawahi and Hancock, 1998), Heteroconium chaetospira (Narisawa et al, 2002), Talaromyces flavus and Trichoderma spp.…”
Section: Biological Controlmentioning
confidence: 99%
“…Metam sodium reduced levels of V. dahliae inoculum in potato field experiments by 60-80 %, and shank injection was more effective than chemigation (Overman, 1982). As metam sodium and methyl-bromide have been phased out, no soil fumigants are currently available for the control of Verticillium wilt diseases in the risk assessment area (Subbarao, 2002;Angelopoulou et al, 2014).…”
Section: Chemical Controlmentioning
confidence: 99%